(untitled) (Research, Society and Development, 2021)
Orthopedic trauma is of great importance in health-disease processes worldwide, with critical consequences for the health of the population. Mainly, when a limb with an important functional biomechanical characteristic is affected, as in forearm fractures. Therefore, the research aims to analyze the profile of trauma patients and forearm fractures in an urgent and emergency service in Porto Velho. As a quantitative, descriptive and retrospective cross-sectional epidemiological study during the period of January and February 2021, which gathered data from the medical records of an urgent and emergency hospital in Rondônia, the research was submitted and authorized by the research ethics committee and experimentation on humans. The profile of trauma victims is predominantly male, 64.61% (42/65), with a bimodal age group of 31-40 years and 51-60 years. With trauma mechanisms poorly described in medical records 20% (13/65), the profile of fractures occurred with a prevalence of isolated fractures of the radius 75.38% (49/65), especially in the distal bone region 85.71% ( 42/49), when compared to isolated ulna fractures 20% (13/65) that had a predilection for diaphyseal fractures 61.53% (8/13). The average length of stay was 3.07, with the highest number of green admissions (1-3 days). Furthermore, of the conducts performed, the surgical one was most chosen 63.07% (41/65), using Kirchner wires 73.17% (30/41). Thus, in the work by Ryan et al. (2010), the proportion between the sexes was 63.6% for males and 36.4%, in line with what was demonstrated by this one, with similar data. The study differed from that carried out by Oliveira et al. (2020), with an average length of stay of 8.19 days, but maintained similarity with the main choice of treatment, 74.8% being surgical. Although Chaudhry et al., (2015) and Woolnough et al., (2020) have shown that surgery using plates and screws has a better functional result and a lower risk of complications, it was still the least chosen surgical choice with 26.82 % (11/41). It is therefore concluded that the study was effective in its type of analysis, with a survey of relevant variables for the profile of affected patients and forearm fractures.